ESCAPE CLAUSES AND TARGETING OF THE REAL EXCHANGE RATE: THE CASE OF NOMINAL EXCHANGE RATE PEGGING - GONZALEZ M,PABLO (ILADES. Universidad Alberto Hurtado., 2010)
We consider an economy under a fixed exchange rate system, but with bounds (a minimum level or a band) on the real exchange rate. The international price of the tradable good is characterized by the continuous arrival of shocks that change its level. In a model with microfoundations, we investigate the effects of targeting the real exchange rate through nominal exchange rate changes that preclude the real exchange from trespassing the imposed bounds. A stochastic general equilibrium model with two goods and fixed non-tradable goods price level is developed. We analyze the cases in which a lower bound or a band on the real exchange rate is introduced. The general conclusion is that when bounds are established, then welfare effects can be expected, which are generated at the expense of the levels of consumption that go in the opposite direction than what the policy intended. This short-run effect is present even in the case the targeting policy is never exercised. This result is similar to the one we find in the target zones literature, in the sense that just the existence of this tolerance band changes the behavior of the economy. An interesting result is that, in the case in which home goods prices are fixed, the imposition of the band on the real exchange rate does not change its behavior within the band. However, this result is not true of other real variables in the economy. In other words, although the targeted variable within the band behaves identically to the case in which there are no bounds, the rest of the real variables in the economy behave differently, even if the targeted variable remains within the band and the escape clause is not triggered.